Wayfinding behavioral patterns of seniors with dementia: two exploratory case studies - Buuren, Leonie van; Derks, Daantje; Mohammadi, Masi; Colenbrander, Bernard (Frontiers in Dementia, 2025)
IntroductionWhile wayfinding is vital for quality of life, it is also a declining skill for people with dementia. Understanding wayfinding behavioral patterns of people with dementia helps to improve the nursing home corridor designs to facilitate autonomously conducting activities of daily life. However, a comprehensive image of these patterns is lacking.MethodsAn empirical qualitative study was conducted, studying seven wayfinding behavioral patterns of people with advanced dementia (n = 8) in two nursing home corridors where they live, using fly-on-the-wall observation.ResultsThe data show that the most frequent wayfinding behavioral patterns observed were “movements” followed by “looking at”, “stops on the route”, and “verbal navigational cues”.DiscussionThese behaviors occurred often at crossroads; i.e., places in which participants should make a decision concerning continuing their route. Spatially, these places have high-visibility values and many things to see for people with dementia. Contradictory, these places might cause more confusion for people with dementia. Therefore, special attention should be paid to the design of these spaces.